2003
DOI: 10.1097/00006982-200306000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Result of Early Vitrectomy for Endogenous Klebsiella Pneumoniae Endophthalmitis

Abstract: Physicians should be alerted to the development of endogenous endophthalmitis in patients with Klebsiella septicemia, especially in diabetics with a hepatobiliary abscess. Aggressive therapy, including early vitrectomy with antibiotic injection, may improve the final outcome in this otherwise devastating ocular condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
94
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(96 citation statements)
references
References 8 publications
1
94
0
1
Order By: Relevance
“…However, overall, irrespective of causative organism, and similar to previous reports on EE, there were poor visual outcomes in this series. 5,8,10,24 Certainly, final VA is often dependent on the vascular inflammatory response, which may be severe and result in long-term sequelae, even in those successfully managed with tap and injection alone. Klebsiella species identification, or demonstration of a liver abscess, in particular, in association with diabetes mellitus, may necessitate early vitrectomy, as demonstrated in this series and previous studies because of the aggressive nature of this microbe and poor outcomes, 10,12,13 however, it remains unclear whether early vitrectomy would salvage these eyes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, overall, irrespective of causative organism, and similar to previous reports on EE, there were poor visual outcomes in this series. 5,8,10,24 Certainly, final VA is often dependent on the vascular inflammatory response, which may be severe and result in long-term sequelae, even in those successfully managed with tap and injection alone. Klebsiella species identification, or demonstration of a liver abscess, in particular, in association with diabetes mellitus, may necessitate early vitrectomy, as demonstrated in this series and previous studies because of the aggressive nature of this microbe and poor outcomes, 10,12,13 however, it remains unclear whether early vitrectomy would salvage these eyes.…”
Section: Discussionmentioning
confidence: 99%
“…The role of vitrectomy in EE is controversial, with published studies often referring to the Endophthalmitis Vitrectomy Study visual acuity (VA) thresholds, which may not be applicable to EE, a disease with a very different pathogenesis and natural history to postsurgical endophthalmitis. [8][9][10][11] Historically, the visual outcomes following EE have been poor, particularly when the causative organism is identified as one of the Klebsiella species. 12,13 Few large case series have documented the incidence, clinical features, and outcomes of EE.…”
Section: Introductionmentioning
confidence: 99%
“…In cases of posttraumatic endophthalmitis where the eye contains retained IOFBs, immediate vitrectomy and intravitreal antibiotic injection has been recommended (Abu El-Asrar, et al, 1999). For endogenous endophthalmitis, adjunct vitrectomy conferred significant improvements in vision, but any delay in vitrectomy resulted in a comparative loss of visual acuity (Yoon, et al, 2003). Most reports agree that vitrectomy should be performed without delay in severe cases of endophthalmitis, especially those involving IOFBs.…”
Section: Therapeutic Challengesmentioning
confidence: 99%
“…Okada et al 25 , Wong et al 29 and Jackson et al 30 stressed the main risk of diabetes contributing to the infection. Chen et al 31 and Yoon et al 10 reported liver abscess as the most frequent source of endogenous endophthalmitis, with Klebsiella pneumoniae as the most common pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…It may be indicated too, in patients with proliferative diabetic retinopathy for conditions connected to repeated intravitreal hemorrhage, tractional retinal detachment, traction-rhegmatogenous retinal detachment and tractional retinal detachment with neovascular glaucoma 6,7 . The literature also mentions the antimicrobial activity of silicone oil which may improve the surgical treatment of endophthalmitis [8][9][10] . At present, a large number of silicone oil variants which differ in viscosity and specific gravity, are available for use in vitreoretinal surgery.…”
Section: Introductionmentioning
confidence: 99%